Ethical Considerations in AI-Driven Personalization for eCommerce Platforms - Siddharth Gupta (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article explores the critical ethical considerations surrounding AI-driven personalization in eCommerce platforms. It delves into the complexities of privacy and data protection, examining the challenges of data collection practices and regulatory compliance in an increasingly data-driven marketplace. The paper addresses the pervasive issue of algorithmic bias, discussing its potential impacts on product recommendations and pricing, while proposing methods for detection and mitigation. Transparency and accountability in AI systems are thoroughly examined, emphasizing the importance of clear communication and explainable AI in building consumer trust. The article also navigates the delicate balance between personalization and consumer autonomy, considering the ethical implications of nudge techniques and strategies to preserve user agency. Finally, it outlines practical approaches for implementing ethical AI in eCommerce, including the development of ethical guidelines, regular system audits, and collaboration with ethicists and consumer advocates. This comprehensive analysis provides valuable insights for eCommerce platforms seeking to harness the power of AI while maintaining ethical standards and fostering consumer trust in the digital retail landscape.